Lipopolysaccharide antigenic relationship between Campylobacter jejuni and Vibrio cholerae (NAG) (World Journal of Experimental Biosciences, 2013)
Lipopolysaccharide was extracted from Campylobacter jejuni and Vibrio cholerae (NAG) by EDTA-heating method. Anti-sera against both LPS was raised in rabbit. Passive hemagglutination was used to check the LPS-antigenic relationship between both bacterial species. The results showed that there is no cross reaction relationship between LPS of C. jejuni and LPS of V. cholerae